2012
DOI: 10.1016/j.apenergy.2011.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Review on thermal energy storage with phase change materials (PCMs) in building applications

Abstract: Thermal energy storage with phase change materials (PCMs) offers a high thermal storage density with a moderate temperature variation, and has attracted growing attention due to its important role in achieving energy conservation in buildings with thermal comfort. Various methods have been investigated by previous researchers to incorporate PCMs into the building structures, and it has been found that with the help of PCMs the indoor temperature fluctuations can be reduced significantly whilst maintaining desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
612
0
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,458 publications
(628 citation statements)
references
References 100 publications
6
612
0
10
Order By: Relevance
“…Zhang et al [41] used silicon dioxide (SiO 2 ) to encapsulate n-octadecane and achieved thermal of about 0.6547 W/m·K. Pan et al [42] used aluminium hydroxide (Al(OH) 3 ) to encapsulate palmitic acid (PA) and obtained thermal conductivities ranging between 10 0.7-0.84 W/m·K. Li et al [43] reported another development also based on silicon dioxide as the shell and paraffin as the core material.…”
Section: Interfacial Polycondensationmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhang et al [41] used silicon dioxide (SiO 2 ) to encapsulate n-octadecane and achieved thermal of about 0.6547 W/m·K. Pan et al [42] used aluminium hydroxide (Al(OH) 3 ) to encapsulate palmitic acid (PA) and obtained thermal conductivities ranging between 10 0.7-0.84 W/m·K. Li et al [43] reported another development also based on silicon dioxide as the shell and paraffin as the core material.…”
Section: Interfacial Polycondensationmentioning
confidence: 99%
“…Although high thermal conductivity inorganic shells i.e. Al(OH) 3 and SiO 2 have been used for thermal enhancement their presence did reduce the overall energy storage capacities of the phase change materials. …”
Section: Shell Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding building applications, PCMs should have a melting/solidification temperature in the practical range of application, high latent heat of fusion and improved thermal conductivity [9]. PCMs should also have desirable thermophysical, kinetic, chemical, economic and environmental properties, as pointed out by several authors [9,[78][79][80][81][82][83][84][85][86]. The optimum incorporation of PCMs within construction systems and the evaluation of the energy performance of the building with these elements is very complex and challenging.…”
Section: Phase Change Materialsmentioning
confidence: 99%